Definition of key players in the formation of a company competitiveness (Путеводитель предпринимателя, 2020)
The article deals with key players of business, whose interests are to ensure the competitiveness of enterprises. A brief overview of the main indicators of all participants at the micro and macro. On the basis of Laferra shows a possible inefficiency of the chosen enterprise development strategies.